Evaluation System and Empirical Research of Brand IP Content Power of Metal Assembly Model Toys - Xi, Wang(시왕); Han, Hyun Suk(한현석) (Journal of Basic Design & Art, 2024)
The aim of this study is to develop and validate a comprehensive assessment system to assessthe intellectual property (IP) content strength of metal assembly toy brands, with a particularfocus on their market influence and competitive advantage. The research process begins with theanalysis of the intellectual property content of 28 well-known metal model assembly toy brandsin the international market, and the correlation characteristics are carefully determined throughcontent analysis. By synthesizing previous academic research results and industry insights, thisstudy constructs a complete comprehensive evaluation system. The system covers thefundamental aspects of the intellectual property content of metal assembled toys, includingoriginality, sharing, convertibility, connectivity and symbolism. In order to ensure the integrityand applicability of the system, this study conducted a rigorous empirical study to verify itsreliability and validity. In addition, the study also explores the subtle relationship between the IPcontent of metal assembled toy brands and consumer preferences, and finds that the intensity ofIP content significantly affects consumer preferences, especially the sharing effect and symboliceffect. The results of this study provide important theoretical and empirical support for theevaluation and strategic development of the intellectual property content of metal assembled toybrands, and provide support and insights for academic research and practical applications in sometoy-related industries. The study highlights the critical role of intellectual property content inshaping consumer perceptions and driving market success, emphasizing that the findings can beeffectively used to assess the deeper connotations of the intellectual property of metalassembled toy brands and provide a theoretical framework for the strategic shaping andoperational management of the intellectual property of metal assembled toy brands in relevantand highly competitive markets. KCI Citation Count: 0